ANALISIS PENERAPAN DEBT FINANCING PEMBIAYAAN MURABAHAH PADA BANK SYARIAH DI INDONESIA - Nursalim, Eko (At-Tawazun, Jurnal Ekonomi Syariah, 2019)
Accounting guidelines for Islamic banking in Indonesia, refer to Statement of Financial Accounting Standard Number 59 concerning accounting for Islamic banking. Furthermore, this guideline is explained by the existence of 2003 Islamic Banking Accounting Guidelines issued by Bank Indonesia. This guide contains all matters relating to Islamic banking accounting. One of them is the accounting guide of Islamic banking products. As the Islamic financing trend in Islamic banking is still dominated by debt financing with murabahah products. Looking at the projected future debt financing trend, namely that most of Indonesia's population is consumptive as the most urgent need is housing. So customers who will file murabahah financing should already know the terms and procedures for submission.